A Short Introduction to International Law - Jouannet, Emmanuelle 1962- (Cambridge University Press, 2014)
In our globalised world the sources and actors of international law are many and its growth prolific and disorderly. International law governs the actions of states on matters as long-established as diplomatic immunity or as recent as the War on Terror, and it now impacts upon the lives of ordinary citizens in areas as diverse as banking and investment, public health and the protection of the environment. In this accessible introduction Emmanuelle Tourme Jouannet explains the latest developments in international law in the light of its history and culture, presenting it as an instrument both for dominance and for change that adjusts and balances the three pillars of the United Nations Charter: the prohibition of the use of force; economic, social and sustainable development; and human rights
Title from publisher's bibliographic system (viewed on 12 Feb 2016)
Keywords: Internationales Recht; International law; Völkerrecht; Einführung; Lehrbuch